Transforming Islamic Education in Schools: Challenges and Opportunities in the Era of Society 5.0 - Zainuddin; Muhammad Wahyudi; Zaimuddin; Ferry Haryadi (PT. PENERBIT TIGA MUTIARA, 2024)
This research analyzes the challenges and opportunities of Islamic education in schools in the Society 5.0 era, which is characterized by the use of industrial revolution 4.0 innovations to overcome social problems. Using a qualitative approach with literature study methods and content analysis, this research examines literature related to the problems of Islamic religious education in schools. The research results identified six main challenges: limited infrastructure, inadequate conditions in rural schools, lack of technology-based learning media, lagging behind in the development of science and technology, use of traditional learning methods, and weak quality of human resources in mastering learning technology. In conclusion, the transformation of Islamic education in the Society 5.0 era requires improving the quality of human resources in learning technology, the use of digital books and technology-based learning media. Systematic efforts are needed to overcome the technology gap and increase the competitiveness of Islamic education in this era.